Pony problems - Keene, Carolyn; Pamintuan, Macky (New York : Aladdin Paperbacks, 2006)
Nancy Drew and her friends George and Bess try to discover how Buttons, the new Shetland pony at the zoo, continues to escape from his pen.
3.9
K-3
K-3
710
Keywords: Drew, Nancy (Fictitious character) -- Fiction; Ponies -- Fiction; Petting zoos -- Fiction; Mystery and detective stories; Drew, Nancy (Fictional character) -- Fiction; Ponies -- Fiction; Petting zoos -- Fiction; Mystery fiction